RAPD Analysis in Sorghum [Sorghum bicolor (L.) Moench] Accessions - Sinha, Sweta; Kumaravadivel, N.; Eapen, Susan (International Journal of Bio-resource and Stress Management, 2023)
Genetic diversity is essential for the continued progress in breeding and to meet future environmental challenges. The present study was conducted to assess the genetic diversity among forty sorghum accessions using RAPD markers. A total of 107 polymorphic loci generated 65.35% polymorphism. The number of markers per primer ranged from 6-12. PIC value ranged from 0.34 to 2.54. Jaccard’s similarity coefficient values ranged from 0.40 to 0.78. The cluster analysis resulted in five clusters revealing high homology between B-lines and R-lines. The clustering pattern of accessions also indicated that there was a wide genetic diversity between the grain sorghum groups and the forage sorghum groups. The variation was moderate among the sweet sorghum. The mutant lines showed more DNA polymorphism compared to the parents. Thus, RAPD analysis revealed the existence of a wide genetic diversity among the sorghum accessions providing scope for the development of well-defined heterotic groups for this crop.